Raspberry Ketone Analogs: Vapour Pressure Measurements and Attractiveness to Queensland Fruit Fly, Bactrocera tryoni (Froggatt) (Diptera: Tephritidae). - Soo J Park; Renata Morelli; Benjamin L Hanssen; Joanne F Jamie; Ian M Jamie; Matthew S Siderhurst; Phillip W Taylor (PLoS ONE)
The Queensland fruit fly, Bactrocera tryoni (Froggatt) (Q-fly), is a major horticultural pest in Eastern Australia. Effective monitoring, male annihilation technique (MAT) and mass trapping (MT) are all important for control and require strong lures to attract flies to traps or toxicants. Lure strength is thought to be related in part to volatility, but little vapour pressure data are available for most Q-fly lures. Raspberry ketone (4-(4-hydroxyphenyl)-2-butanone) and analogs that had esters (acetyl, difluoroacetyl, trifluoroacetyl, formyl, propionyl) and ethers (methyl ether, trimethylsilyl ether) in replacement of the phenolic group, and in one case also had modification of the 2-butanone side chain, were measured for their vapour pressures by differential scanning calorimetry (DSC), and their attractiveness to Q-fly was assessed in small cage environmentally controlled laboratory bioassays. Maximum response of one category of compounds, containing both 2-butanone side chain and ester group was found to be higher than that of the other group of compounds, of which either of 2-butanone or ester functionality was modified. However, linear relationship between vapour pressure and maximum response was not significant. The results of this study indicate that, while volatility may be a factor in lure effectiveness, molecular structure is the dominating factor for the series of molecules investigated.